A Randomized Clinical Trial of the Effect of an Angina Self-Management Intervention on Health Outcomes of Patients With Coronary Heart Disease. Issue 5 (September 2018) - Kimble, Laura P.
Abstract: Purpose: The aim of this study was to test the effect of a psychoeducational intervention to enhance angina pectoris (AP) symptom self-management. Design: A two-group, single-blind, randomized controlled trial. Methods: Following institutional review board approval, a convenience sample of cardiac inpatients was recruited. Within 2 weeks following discharge, the Angina Self-Management (ASM) intervention group ( n = 39) received a nurse-delivered, telephone intervention focused on AP symptom monitoring and management. The control group ( n = 41) received an attention-control telephone call. Physical function, anxiety, and angina frequency were assessed between 3 and 6 months postintervention. Findings: Men in the ASM group ( n = 24) reported better physical function and lower anxiety than men in the control group ( n = 26). Women in the ASM group ( n = 15) reported worse physical function and higher anxiety than women ( n = 15) in the control group. Conclusions: Angina symptom monitoring may be more difficult for women. Rehabilitation nurses should be proactive in addressing issues associated with women's AP symptom management.